PENGARUH VIDEO PEMBELAJARAN TERHADAP EFEKTIVITAS BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA KELAS X SMA NEGERI 2 TARUTUNG KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2018/2019 - harion hutauruk (IAKN Tarutung, 2019)
vAbstract, This study aims to find out how much positive and significant influence between the use of learningvideos by Christian Education Teachers on the effectiveness of learning in class X Tarutung 2 High SchoolNorth Tapanuli Regency, with the hypothesis there is the Effect of Learning Videos on Learning Effectiveness ofClass X Students of State High School 2 Tarutung North Tapanuli Regency 2018/2019.This research uses inferential quantitative descriptive approach, with a population of all students of class XTarutung 2 High School totaling 288 people with a sample of 40 people. Data was collected by a closedquestionnaire of 30 items compiled by the author based on variable indicators according to expert theory. Thequestionnaire trial was conducted on 30 students who were not research respondents, and validity andreliability were tested. The results of data analysis show that there is a positive and significant influencebetween Learning Videos on Learning Effectiveness of Class X Students of Tarutung 2 High School NorthTapanuli Regency 2018/2019 with a coefficient of determination (r2) = 38.68% and significant test of influenceobtained by Fcount Ftable of 23.77 4.10, meaning that Ho is rejected and Ha is accepted.Keywords: Learning Videos, Learning Effectiveness.